Towards Artifactual Literacies: A Content Analysis of Secondary School History Curricula in Canada - Heydon, Rachel; Akiwenzie, Elizabeth; McKee, Lori; Poczobut, Sandra; Seabrook, Fred; Zhang, Zheng (Journal of Teaching and Learning, 2026)
The literature recognizes the benefits of teaching with artifacts, but questions about how artifacts might be situated within curricula and with what implications arise. To explore these questions within a settler-colonial context, this study conducted a content analysis of programmatic history curricula in Canada, focusing on teaching the World Wars with artifacts. Informed by an orientation of artifactual literacy and a collaborative research protocol guided by an Indigenous cultural educator, the study found that programmatic curricula call for the use of artifacts but provide a dearth of guidance on how artifacts might be conceptualized or the literacy or pedagogical requirements for making meaning with them. The study recommends that programmatic curricula include teaching and learning with artifacts and do so within a framework that acknowledges artifactual literacies and provides support for the ethical use of artifacts with special attention to responsibilities in a settler-colonial context.